2016
DOI: 10.3390/nano6010016
|View full text |Cite
|
Sign up to set email alerts
|

Resistive Switching of Plasma–Treated Zinc Oxide Nanowires for Resistive Random Access Memory

Abstract: ZnO nanowires (NWs) were grown on Si(100) substrates at 975 °C by a vapor-liquid-solid method with ~2 nm and ~4 nm gold thin films as catalysts, followed by an argon plasma treatment for the as-grown ZnO NWs. A single ZnO NW–based memory cell with a Ti/ZnO/Ti structure was then fabricated to investigate the effects of plasma treatment on the resistive switching. The plasma treatment improves the homogeneity and reproducibility of the resistive switching of the ZnO NWs, and it also reduces the switching (set an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…[171][172][173][174][175][176][177][178][179] Even if resistive switching was previously observed in ZnO thin films grown by different techniques, [180][181][182] resistive switching in single crystalline ZnO nanowires with wurtzite structure grown by VLS technique was reported for the first time in 2011 by Chiang et al [171] In this case, the Ti/ZnO NW/Ti devices exhibited two well defined resistance states with high performances in terms of HRS/LRS ratio that was reported to be as high as 7.7 × 10 5 with an endurance of 100 cycles. [171][172][173][174][175][176][177][178][179] Even if resistive switching was previously observed in ZnO thin films grown by different techniques, [180][181][182] resistive switching in single crystalline ZnO nanowires with wurtzite structure grown by VLS technique was reported for the first time in 2011 by Chiang et al [171] In this case, the Ti/ZnO NW/Ti devices exhibited two well defined resistance states with high performances in terms of HRS/LRS ratio that was reported to be as high as 7.7 × 10 5 with an endurance of 100 cycles.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
See 1 more Smart Citation
“…[171][172][173][174][175][176][177][178][179] Even if resistive switching was previously observed in ZnO thin films grown by different techniques, [180][181][182] resistive switching in single crystalline ZnO nanowires with wurtzite structure grown by VLS technique was reported for the first time in 2011 by Chiang et al [171] In this case, the Ti/ZnO NW/Ti devices exhibited two well defined resistance states with high performances in terms of HRS/LRS ratio that was reported to be as high as 7.7 × 10 5 with an endurance of 100 cycles. [171][172][173][174][175][176][177][178][179] Even if resistive switching was previously observed in ZnO thin films grown by different techniques, [180][181][182] resistive switching in single crystalline ZnO nanowires with wurtzite structure grown by VLS technique was reported for the first time in 2011 by Chiang et al [171] In this case, the Ti/ZnO NW/Ti devices exhibited two well defined resistance states with high performances in terms of HRS/LRS ratio that was reported to be as high as 7.7 × 10 5 with an endurance of 100 cycles.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…The authors showed that Ar plasma treatments resulted in lower threshold voltages and increased conductance, while higher threshold voltages were observed after oxygen plasma treatments. [176] Another approach based on hydrogen annealing treatment of ZnO nanowires was proposed by Lee et al [177] After the growth process, ZnO NWs were annealed at 350 °C for 30 min in a H 2 /Ar mixture ambient. The effects of plasma were further discussed by Lai et al in their works [175,176] where authors suggested that a low cost Ar plasma treatment (100 W at 100 Pa, for 60/240 s) can enhance repeatability and decrease SET and RESET voltages in single isolated ZnO NWs grown by VLS method.…”
Section: Surface Treatmentsmentioning
confidence: 99%
“…Zinc oxide (ZnO), which is a well-known oxide semiconductor, has also been widely studied because of its resistance switching (RS) behaviors [48]. ZnO-based RRAM devices have been reported to show an ultrafast programming speed of 5 ns, an ultrahigh ON/OFF ratio of 10 [7], a long retention time of more than 10 7  s, and high reliability at elevated temperatures [2, 5].…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, most ReRAM devices based on nanowires exhibited an endurance of less than 100 switching cycles, as shown in Table S1 of the Supporting Information. [11,14,15,[31][32][33][34][35] The I-V curves of the SET process and RESET process over 205 cycles are shown in Figure 2a,b, respectively. The compliance current (Icc) was set as 10 −5 A to prevent the breakdown of the devices due to excessive current passing through the devices.…”
mentioning
confidence: 99%